Music Going for a Song: Protecting creative content could promote development in the digital age - Kabanda, Patrick (Finance & Development, 2016)
Intellectual property rights date to ancient Egypt. In an inscription on a rare Egyptian tablet from 2000 BCE displayed at the Louvre in Paris, Irtysen, a master crafts man, scribe, and sculptor, boasts about his trade secrets. How would he maintain ownership of his techniques and make a decent living in today’s digital world?Technology occupies us in ways that would baffle Irtysen. Rush hour subway riders swipe and text away while digital music blasts through their earphones. Whether they’re consuming this music legally or illegally, who knows? What’s clear is technology makes it easy to copy and transmit creative work: capture and share are the order of the day